Nurses' perspectives on the work process in primary health care: challenges and perspectives (Research, Society and Development, 2022)
Introduction: The health work process is configured as a systematic organization of different activities and actors, fostered by decision-making that aims to ensure the success of necessary and priority actions and interventions in health services. Objective: The objective was to characterize the work process in the Family Health Strategy from the perspective of the nurse, with emphasis on the main challenges and perspectives. Method: Descriptive study with a quantitative and qualitative approach, whose population was nurses from the Family Health Strategy in a municipality in the interior of Tocantins, Brazil. Data were collected through a questionnaire, analyzed quantitatively by relative and absolute frequencies, and qualitatively by categorical critical analysis. Results and Discussion: The nurses' perception of the work process in the ESF was characterized according to the thematic cores: “How do I work? How do I articulate the actions and the team? How do I rate what I do? How do I improve the work?”. Conclusion: The main challenges highlighted are related to professional training, the management of work and personnel dynamics, and the pre-established model in the public health system. The perspectives lie in the potential for change and updating, as well as in the systematization of the planning and evaluation of the work process.